Optimizing the vibration responses of spray boom suspension system by artificial neural network method - Tahmasebi, Mona (2011)
One of the most vital problems in agricultural operation is crop protection against pests, insects, weeds, and diseases that the crop sprayers are used to spread chemicals on the field. Motion on the uneven fields leads to unwanted vibration on sprayer booms, and the uniformity of distribution pattern are changed. Reduction of this undesired motion of sprayer boom needs a mechanism between spray boom and tractor chassis. In this research, a passive spray boom suspension was considered to remove vertical vibration. The natural frequencies and mode shapes of boom were obtained by simulation in ABAQUS software. Next, system modeled in Working Model 2D to obtain the response of system exposed to harmonic vibration. To optimize the vibration transmissibility from tractor to boom, artificial neural network (ANN) was used. In this method, for minimizing the vibration responses of the boom were considered as examples to enter in ANN. Finally, mechanical impedance of boom was minimized by ANN. The results lead to find the best values for spring and damper coefficients to set in real system. In evaluation step, system was modeled again in Working Model with new obtained parameter, and the efficiency of that was measured. The results of evaluation showed this modified suspension system can remove vibration of spry boom with acceptable efficiency.